Erythrocyte transketolase activity, markers of cardiac dysfunction and the diagnosis of infantile beriberi. - Douangdao Soukaloun; Sue J Lee; Karen Chamberlain; Ann M Taylor; Mayfong Mayxay; Kongkham Sisouk; Bandit Soumphonphakdy; Khaysy Latsavong; Kongsin Akkhavong; Douangkham Phommachanh; Vanmaly Sengmeuang; Khonsavanh Luangxay; et al. (PLoS Neglected Tropical Diseases)
Background Infantile beriberi is a potentially lethal manifestation of thiamin deficiency, associated with traditional post-partum maternal food avoidance, which persists in the Lao PDR (Laos). There are few data on biochemical markers of infantile thiamin deficiency or indices of cardiac dysfunction as potential surrogate markers. Methodology/principal findings A case control study of 47 infants with beriberi and age-matched afebrile and febrile controls was conducted in Vientiane, Laos. Basal and activated erythrocyte transketolase activities (ETK) and activation (α) coefficients were assayed along with plasma brain natriuretic peptide, N-terminal pro-brain natriuretic peptide and troponin T. Basal ETK (and to a lesser extent activated ETK) and plasma troponin T were the only infant biochemical markers that predicted infantile beriberi. A basal ETK ≤ 0.59 micromoles/min/gHb gave a sensitivity (95%CI) of 75.0 (47.6 to 92.7)% and specificity (95%CI) of 85.2 (66.3 to 95.8)% for predicting infantile beriberi (OR (95%CI) 15.9 (2.03-124.2); p = 0.008) (area under ROC curve = 0.80). In contrast, the α coefficient did not discriminate between cases and controls. Maternal basal ETK was linearly correlated with infant basal ETK (Pearson's r = 0.66, p < 0.001). The odds of beriberi in infants with detectable plasma troponin T was 3.4 times higher in comparison to infants without detectable troponin T (OR 3.4, 95%CI 1.22-9.73, p = 0.019). Detectable troponin T had a sensitivity (95%CI) of 78.6 (59.0 to 91.7) % and specificity (95%CI) of 56.1 (39.7 to 71.5) % for predicting infantile beriberi. Conclusions/significance Basal ETK is a more accurate biochemical marker of infantile beriberi than the activation coefficient. Raised plasma troponin T may be a useful indicator of infantile beriberi in infants at risk and in the absence of other evident causes.